Therapeutic efficacy and safety of radiofrequency ablation for the treatment of trigeminal neuralgia: a systematic review and meta-analysis - Wu H (Journal of Pain Research, 2019)
Huiqun Wu,1,* Ju Zhou,1,* Jialu Chen,1 Yuwei Gu,1 Lili Shi,1 Haosheng Ni21Department of Medical Informatics, Medical School of Nantong University, Nantong 226001, People’s Republic of China; 2Department of Otorhinolaryngology, Affiliated Hospital of Nantong University, Nantong 226001, People’s Republic of China*These authors contributed equally to this workObjective: The objective of this study was to summarize the effectiveness and safety of trigeminal neuralgia (TN) treatment via different radiofrequency approaches such as continuous radiofrequency (CRF), pulsed radiofrequency (PRF), and combined CRF and pulsed radiofrequency (CCPRF) treatments, thus providing high-quality clinical evidence for TN treatment.Methods: A series of databases were searched for relevant articles published between January 1998 and April 2018. The modified Jadad scale was referred to evaluate the methodological quality of the included studies. Data were extracted independently, and the outcome and safety of different routes, temperatures, and guidance used in CRF, PRF, and CCPRF were compared. Meta-analysis and publication bias were calculated using Review Manager software.Results: In total, 34 studies involving 3,558 participants were included. With regard to TN treatment, PRF had no difference in cured rate in comparison with CRF, while CRF was more effective than CCPRF (P<0.05). The comparison of complication rates showed that PRF and CCPRF were safer. For puncture guidance via CRF, three-dimensional-printed template was more accurate in success rate at first puncture than computed tomography guidance (P<0.05). For puncture route, foramen rotundum (FR) or pterygopalatine fossa (PPF) route had no significance in efficiency rate via CRF in comparison with foramen oval (FO) route, but PPF and FR routes were safer. For CRF treatment, low temperature (68°C–70°C) compared with high temperature (71°C–75°C) had no effect. Moreover, higher temperature (66°C–80°C) had a greater effect compared with lower temperature (55°C–65°C) on TN treatment (P<0.05), while the safety of which was decreasing.Conclusion: CCPRF could achieve a greater effect and safety on TN treatment. FR and FO routes in TN puncture treatment via CRF are safer. Medium temperature range is better for CRF therapy, and higher temperature is recommended in PRF, especially for the elders. Further international multicenter trials are needed to confirm the evidence.Keywords: trigeminal neuralgia, radiofrequency ablation, radiofrequency thermocoagulation, meta-analysis